(untitled) (Academia Science Repository, 2023)
In this article, it is very difficult to take into account the unique nature of the child. Because even children of the same age can be mentally different. M: ability to see and hear, activity, quick perception, slow thinking, calmness or restraint, talkative or lack of speech, lively or lack of enthusiasm, lazy or Diligence, laziness and half-working, compactness or quickness to work are the effects of the nervous system, and the teacher should know them.